Interactive Video Aided Interactional on Students’ Listening Skill - Dicky Pamungkas; Zohri Hamdandi; Candraning Prihatini (Syntax Idea)
This research aimed to investigate the effect of interactive video on students' listening skills of the seventh grade at SMPN 1 Gedung Surian and to know where the better media used interactive or Powerpoint media in teaching listening skills. The research employed a quasi-experimental design with a pre-test post-test control group. The sample of this research consisted of 60 seventh-grade students who were cluster random sampling selected and divided into two groups: experimental group and control group. The experimental group was taught using interactive video, while the control group was taught using conventional methods. Data were collected through a listening test before and after the treatment. The data were analyzed using independent samples t-test. The results showed that the experimental group's mean score (73.67) was significantly higher than the control group's mean score (47.23) with a p-value of 0.000. The findings indicated that the use of interactive video had a positive effect on students' listening skills, and as the result of the mean score of both classes the interactive video was more significant than PowerPoint media. Therefore, it is recommended that English teachers use interactive videos as a teaching method to improve students' listening skills.